Phytochemical profiles and antioxidant activities of four Cannabis sativa cultivars in Thailand - SUWADEE CHOKCHAISIRI; UTUMPORN NGIVPROM; PIYATHIDA PHATTHANAPHONG; KANWIPHA BOON-ORN; SITTICHOK WONGSONTHOM; PALAPON CHIMPALEE (Society for Indonesian Biodiversity, 2026)
Abstract. Chokchaisiri S, Ngivprom U, Phatthanaphong P, Boon-Orn K, Wongsonthom S, Chimpalee P. 2026. Phytochemical profiles and antioxidant activities of four Cannabis sativa cultivars in Thailand. Biodiversitas 27 (1): d270129. https://doi.org/10.13057/biodiv/d270129. Cannabis sativa produces diverse bioactive metabolites, including cannabinoids, phenolics, and flavonoids, which collectively shape its chemical and functional diversity. This study compared four cannabis cultivars cultivated under uniform conditions in Thailand (Sensi Dawg, Top Cherry Gas, Wedding Cake, and Dur Burger) to classify chemotypes and examine cultivar-dependent differences in antioxidant capacity. Ethanolic extracts were analyzed for ten cannabinoids by HPLC, together with Total Phenolic Content (TPC), Total Flavonoid Content (TFC), and antioxidant activities evaluated using DPPH, ABTS, and FRAP assays. Distinct chemotypic differentiation was observed among cultivars. Dur Burger was classified as a CBD-dominant cultivar, with high CBD content, and showed the strongest activity in the ABTS assay. In contrast, Sensi Dawg, Top Cherry Gas, and Wedding Cake were THC-dominant cultivars and exhibited comparatively higher TPC and TFC levels, which were associated with stronger DPPH scavenging and ferric reducing power. Quantitative values are reported on a per-extract basis (mg per g extract). Because individual cannabinoids were not isolated for individual testing, these relationships are interpreted as associations rather than direct mechanisms; proposed links between CBD-rich profiles and ABTS activity are therefore hypotheses consistent with the present data and prior literature, not directly evaluated here. Overall, substantial phytochemical and antioxidant diversity was evident among cultivars. Variation in antioxidant performance reflected not only phenolic and flavonoid abundance but also differences in overall cannabinoid profiles, indicating contributions from multiple metabolite classes. This study addresses a gap in systematic, side-by-side profiling of Thai-grown cannabis by integrating quantitative cannabinoid analysis with multiple antioxidant assays. Key limitations include in vitro testing only, the use of ethanolic extracts from a single indoor location, and the absence of assays on isolated cannabinoids. Nevertheless, the findings provide cultivar-specific reference data to support evidence-based selection of chemotypes for pharmaceutical, nutraceutical, and functional biomaterial applications.